Revolutionising Banking and Finance with Artificial Intelligence Smart Solutions for Digital India - Naidu, Srinivas; Chandra, Bablee; Kishore, M Nanda (International Journal of Advances in Business and Management Research (IJABMR), 2025)
Among the many global businesses that have been profoundly affected by artificial intelligence (AI) are the banking and finance industries. Banking and finance have been at the forefront of AI adoption, which has transformed conventional operations by providing new insights into old challenges, better decision-making, and exceptional customer service. This article delves into the several ways AI may be used in the banking and finance industry, discussing the advantages and disadvantages of this technology. Decisions in risk management, fraud detection, credit scoring, and investment strategies have been made more efficient and precise with the use of AI-powered technologies including machine learning, natural language processing, and predictive analytics. For example, AI models can sift through mountains of data to spot fraudulent activity in real time and forecast market trends both of which drastically cut down on financial losses. With the power of natural language processing, chatbots and virtual assistants have revolutionised customer service. They provide round-the-clock support, personalised suggestions, and instantaneous help. Artificial intelligence (AI) apps improve operational efficiency in the banking industry by automating data input, compliance monitoring, and report production, among other repetitive operations. Automating routine tasks via robotic process automation (RPA) helps cut down on human error, speed up procedures, and save money. Artificial intelligence (AI) helps with regulatory compliance by deciphering complex legal frameworks, which is crucial for keeping up with the ever-changing financial rules. Financial organisations may provide loans with greater accuracy and responsibility with the use of AI algorithms that enhance credit risk assessment, hence minimising default risks. Another domain where AI has shown tremendous promise is investment management. The use of machine learning allows robo-advisors and algorithmic trading to optimise portfolio performance while reducing risk.